DO ALIENS PERFORM CYBER- ATTACKS ON GLOBAL NETWORK? - AKYEŞİLMEN, Nezir (Cyberpolitik Journal, 2023)
The possibility of aliens organizing cyberattacks on our global network is a complex one. There is no evidence that Aliens have ever launched a cyber-attack against us, but there is also no way to know for sure whether they have launched any or not, at least for now? We have also no idea about their technological capacity and capability. Indeed, we are also even not sure about their existence, except for some allegations